The Influence of Calendar of Health As A Prevention of Stunting In Pre-Marriage Couples - Prasetyanti, Dhita Kris; Fitriasnani, Meirna Eka (STRADA : Jurnal Ilmiah Kesehatan, 2020)
To reduce the incidence of stunting, prevention is needed starting from the pre-conception period, one of the preventive efforts with health education using a health calendar. The purpose of this study was to determine the effect of the health calendar as an effort to prevent stunting in premarital couples. This study used a pre-experiment. This study used a pre-experimental design with one group pretest and posttest design. The population in this study were pre-marital couples aged <35 years and had never been married before as many as 16 premarital couples using the total population sampling technique, statistical test using Wilcoxon. There is an effect of the health calendar media on knowledge and attitudes in premarital couples (p-value = 0.001 and 0.003).The results that there is a need for health education using health calendar to increase knowledge and attitudes so that it is expected to change behavior to prevent stunting